ACADEMIC AUTONOMY: RESPONSIBILITY OF THE UNIVERSITY FOR THE QUALITY OF HIGHER EDUCATION - Kalinicheva, Нalyna (Educological discourse, 2022)
Dynamic changes in socio-political life, European integrative aspirations of Ukraine and the development of a democratic society determined a number of reform changes in the system of national higher education, which affected the spread of academic freedoms and the universities institutional autonomy. The article points out the role of university autonomy and its measuring; the content of academic autonomy is revealed; it is the focused on one of its components – the rating assessment of research and teaching staff professional activities. The aim of the article is to determine the role of academic autonomy as a necessary condition for the evaluation of scientific and pedagogical activities of university teachers and justify the importance of such self-esteem in the system of internal quality assurance of higher education. The article points out the connection between the rating assessment of scientific and pedagogical staff of the university with its mission, vision and development strategy. It is noted that the rating of the university teachers’ professional activities is a multilevel, integrated and complex process, which aims to study the level of quality assurance in higher education at the university and develop and justify management decisions to improve it. Based on the comparison of normative documents and open sources on the Internet of Ukrainian universities from different Ukraine regions and universities included in the QS World University Rankings 2022, it was carried out the analysis of the rating assessment the professional activity of research and teaching staff of higher education institutions. The analysis of self-assessment methods made it possible to identify both common criteria and approaches, аnd certain specifics in the rating policy of higher education institutions, which indicates the institutional autonomy of Ukrainian universities. Generalization the rating assessment practice of research and teaching staff in higher education institutions of Ukraine provides a key to understanding the existing problems and unused reserves in the internal system and the process of ensuring the quality of higher education. Further study the practice of teaching staff professional activities' rating assessment in higher education institutions and taking into account the experience will help to optimize the internal providing system of higher education quality.